Guliang Kangin Village Development in Bangli Regency as an Innovative Village Model for Flower Village in the Asian Region - Kartika, I Made; Sumada, I Made; Adnyana, Yudistira; Suwandana, I Made Adi; Utama, I Gusti Bagus Rai (Technium Social Sciences Journal, 2021)
The objectives to be achieved in this study are determining the digital marketing conditions for the tourism flower village in Guliang Kangin Village, determining problems and digital-based development strategies in rural areas, and formulating innovative village development models according to local potential. Guliang Kangin Village Development in Bangli Regency as an Innovative village model towards flower village in the Asian Region is a tourism marketing strategy to meet the target number of tourist visits expected to contribute to the village government and society. The strategy includes planning to identify types of flower plants that will be used as tourist attractions, assisting in mapping the areas that will become Flower Village areas, facilitating proposals for developing Flower Village to the government, developing agricultural innovations according to technology, providing special financial assistance, carrying out training and agricultural cultivation activities. and plantations, building cooperation with related parties.